Pitch Lake, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
This is a vintage postcard showing the pitch lake at La Brea, south west Trinidad. The pitch lake is the largest natural deposit of asphalt in the world and was discovery by Sir Walter Raleigh in 1595. It is mined for asphalt and is a fascinating tourist attraction.
Colour: Sepia; Style: Landscape; Other: Unbordered; Divided
Keywords: Trinidad and Tobago; Postcards; Asphalt industry--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; Pitch; Trees--Trinidad and Tobago; Buildings--Trinidad and Tobago; [1912]; Pitch Lake, The (La Brea)